(untitled) (International Journal of Food and Nutritional Sciences, 2021)
It is widely recognized that when two powerful undesired signals infiltrate a non-linear circuit at the receiver’s input, they can lead to interference at the receiver’s output. In the absence of the desired signal, tuning the receiver reveals both interference signals simultaneously at the output. The non-linear characteristics of specific components, such as transistors and diodes, induce frequency conversion, resulting in the emergence of frequency components that affect the receiver. The issue becomes more pronounced when the sum or difference of interference frequencies aligns with the tuning frequency, amplifying the detrimental effects. In this context, the interference signal, upon generation, undergoes a transformation, converging into an intermediate frequency (fo - Δf), alongside the desired signal. This phenomenon is depicted in Figure 1, illustrating the selectivity variation of an ideal receiver and a V-receiver. This paper delves into the mathematical analysis of the inter modulation phenomenon, aiming to discern the implications of unwanted signal modulation on interference generation. Specifically, the investigation seeks to understand how modulation depth influences the variation of unwanted signals. In conclusion, this study explores the intricate realm of interference effects within nonlinear circuits, caused by potent undesired signals. Through mathematical analysis, the research uncovers the foundations of the inter modulation phenomenon and its implications, with a particular focus on how the modulation depth of unwanted signals shapes the variation process.